Uso de las larvas de moscas soldados negras (Hermetia illucens), como alternativa alimenticia para pollos de engorde - Vivas Silva, Esther Mayra (2024)
In the development of this research based on the "Use of black soldier fly larvae (Hermetia illucens), as an alternative food for broiler chickens." in which it was proposed as an objective, to analyze the advantages of using black soldier fly larvae (Hermetia illucens) as an alternative food applied in the diet of broiler chickens. The methodology, is determined to be based on a basic type of research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development it determined the scale of production of broiler chickens in Ecuador, their nutritional requirement, nutritional value of the larvae, their definition, which ones, and how they act, finally, the optimal levels of incorporation in the feed and its benefits in birds were identified. As for the results, the replacement with black soldier fly larvae applied in the feeding of broiler chickens, have provided an enlightening vision of the strategies implemented by producers, the analysis indicates that adding between 20 and 30 percent of larvae meal to the diet has a significant impact without negatively affecting performance, but if more than 40% is applied there will be digestive problems (diarrhea, indigestion) also accumulation of fats in the tissues, and affect the potability of the feed. In conclusion, they contain a large amount of crude proteins between 40 and 50% of high quality, which are vital for the growth and development of birds. In addition, they provide a variety of micronutrients, such as vitamins such as B2, B5, B7, B9 and minerals that generally range between 20% and 40% of the total diet, can provide significant nutritional benefits..